Microbiota influences host exercise capacity via modulation of skeletal muscle glucose metabolism in mice - Kim, Hye Jin; Kim, Youn Ju; Kim, Yong Jae; Baek, Ji Hyeon; Kim, Hak Su; Kim, Il Yong; Seong, Je Kyung (Experimental & molecular medicine, 2023)
The microbiota enhances exercise performance and regulates host physiology and energy metabolism by producing beneficial metabolites via bacterial fermentation. In this study, we discovered that germ-free (GF) mice had a reduced capacity for aerobic exercise as well as low oxygen consumption rates and glucose availability. Surprisingly, GF mice showed lower body weight gain and lower fat mass than specific pathogen-free (SPF) mice. Therefore, we hypothesized that these paradoxical phenotypes could be mediated by a compensatory increase in lipolysis in adipose tissues owing to impaired glucose utilization in skeletal muscle. Our data revealed that gut microbiota depletion impairs host aerobic exercise capacity via the deterioration of glucose storage and utilization. The improved browning ability of GF mice may have contributed to the lean phenotype and negatively affected energy generation. These adaptations limit obesity in GF mice but impede their immediate fuel supply during exercise, resulting in decreased exercise performance. Gut microbes: unexpected exercise partners Gut microbes alter metabolism and enhance exercise performance in mice. Gut microbes are known to produce beneficial metabolites and improve health, but how they affect exercise is not well understood. Je Kyung Seong at Seoul National University in South Korea and co-workers compared how mice with a healthy microbiome and germ-free (GF) mice responded to exercise. Although GF mice became exhausted much sooner than non-GF mice, spent one-third less time running, and ate 1.5 times more than non-GF mice, they did not gain weight. Further investigation showed that instead of getting their energy from glucose stored in skeletal muscles, GF mice were burning fat, which reduced their performance; reinstating their gut microbes restored their exercise capacity. A healthy gut microbiome is critical for exercise capacity and future work could focus on identifying key microbial species.